2024
DOI: 10.3390/su16031245
|View full text |Cite
|
Sign up to set email alerts
|

ChatGPT: Challenges and Benefits in Software Programming for Higher Education

Carlos Alexandre Gouvea da Silva,
Felipe Negrelle Ramos,
Rafael Veiga de Moraes
et al.

Abstract: ChatGPT is a substantial language model developed by OpenAI, rooted in the GPT-3.5 architecture, with the capacity to generate human-like responses to text-based inputs. ChatGPT serves various purposes, encompassing chatbots, customer service, and personal assistants, which can significantly contribute to sustainability initiatives. Its applications range from language translation and content creation to text summarization. Utilizing ChatGPT offers several advantages, notably its rapid response generation, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…By addressing each student's speci c di culties and misconceptions, this individualized approach increases student engagement and promotes a deeper comprehension of the subject matter (Grassini, 2023). Furthermore, ChatGPT is an excellent tool for students who need immediate assistance or clari cation on complex assignments or topics, encouraging independent and self-directed learning (Xiao & Zhi, 2023;Silva et al, 2024). Additionally, ChatGPT can support collaborative learning by allowing students to participate in insightful conversations and knowledge exchanges in online settings.…”
Section: Potential Bene Ts Of Using Chatgptmentioning
confidence: 99%
“…By addressing each student's speci c di culties and misconceptions, this individualized approach increases student engagement and promotes a deeper comprehension of the subject matter (Grassini, 2023). Furthermore, ChatGPT is an excellent tool for students who need immediate assistance or clari cation on complex assignments or topics, encouraging independent and self-directed learning (Xiao & Zhi, 2023;Silva et al, 2024). Additionally, ChatGPT can support collaborative learning by allowing students to participate in insightful conversations and knowledge exchanges in online settings.…”
Section: Potential Bene Ts Of Using Chatgptmentioning
confidence: 99%
“…For example, Jalil et.al., [29] found that although ChatGPT can respond to 77.5% of the ex-amined questions, it provided correct or partially correct answers in only 56.6% of cases and correct or partially correct explanations in only 53% of cases. Other studies have revealed that ChatGPT can exhibit inaccuracies in mathematical calculations and may also generate errors in algorithms or programming codes [27,30]. Also, the quality of the AI chatbot responses is heavily influenced by the clarity and quality of students' questions and prompts, as clear and well-structured inquiries tend to yield better responses from AI chatbots [11].…”
Section: Contributions To the Acquisition Completion Or Activation Of...mentioning
confidence: 99%
“…The model's ability to process and generate human-like text responses makes it an innovative tool for use in professional settings and diverse educational landscapes. In this context, different authors pointed out that ChatGPT can facilitate teaching and learning by generating quizzes, designing assessment, generating summaries, and translating complex terminologies, illustrating its multifunctional nature and far-reaching impact [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to leverage the benefits of ChatGPT while mitigating its potential risks and ensuring that ethical standards are upheld. Most researchers have stressed the importance of academic integrity and ethical considerations, especially considering the ease with which students might rely excessively on AI for learning and problem-solving [9,30].…”
Section: Introductionmentioning
confidence: 99%